How to Manage a Great Project : On budget. On target. On time. - Clayton, Mike (Pearson, 2014)
So, you've been asked to manage a project. Not sure where to start? Start here. This is your ultimate one-stop, easy-going and very friendly guide to delivering any project of any size. Even if you're a first time, never-done-it-before, newbie project manager, How to Manage a Great Project will get you from start to f.